ANALISIS NILAI OVERALL EQUIPMENT EFECTIVENESS (OEE) SEBAGAI LANGKAH PENINGKATAN EFEKTIFITAS MESIN PELLET MILL DI PT. NI CIBITUNG - Billy Zaelany Purnama (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract Demands for wood pellets as an alternative energy source of thecountry of Taiwan, Japan and Korea became one of the main factors for the PT.NI to increase productivity by utilizing production equipment as effectively aspossible. Implementation of preventive maintenance is still not optimal becausePelletiser still often damaged. Pelletiser damage caused downtime large enoughand also will reduce production capacity, which in turn led to delays in meetingthe needs of consumers.The purpose of this study was to measure the value ofOEE, determine the magnitude of each factor Six big losses that affect the valueof OEE, and analyzes the factors that cause the main as a basis for improvement.Based on data processing, value of OEE is still below the targets to be achievedby the company amounted to 76.95%. From the calculation of the Six Big Losses,factors that provide the most significant influence on the effectiveness of themachine is Equipment Failure . OEE values and Losess Big Six factors are thebasis of the proposed improvements is given to PT.NI.Keyword: Downtime, Equipment Failures Losses, Overall EquipmentEffectiveness, Performance